13.2: 360° Multi‐Faced Tracking and Interaction Using A Panoramic Camera. Issue 1 (June 2015) - Su, Chen; Zhong, Qing; Yu, Chao; Li, Haifeng; Liu, Xu
Abstract : A 360‐degree multi‐faced tracking and interaction method using a panoramic camera is implemented, which can detect and track multiple users around general display to achieve better interaction experience. In the experiment, the panoramic face tracking method is applied to a 360‐degree 3D display system for verification.